Expanding treatment options for patients with HER2+ metastatic breast cancer with margetuximab plus chemotherapy: a case report series - Mahtani, Reshma; Harpalani, Natasha; Yan, Fengting; Phiel, Kristen; Kovalenko, Iuliia (Frontiers in Oncology, 2024)
HER2+ breast cancer (BC) accounts for approximately 14% of total BC cases in the United States; it is highly aggressive, has a high associated risk for mortality, and a poor prognosis. These case reports demonstrate that margetuximab plus chemotherapy is a valid option for patients with HER2+ metastatic (M) BC who have received multiple HER2-targeted agents. Frontiers in Oncology is the great fit for these reports as it provides information in the setting of HER2+ MBC in which more treatment options are needed for patients.